2011
DOI: 10.1007/s11547-011-0676-7
|View full text |Cite
|
Sign up to set email alerts
|

Seven-Tesla micro-MRI in early detection of acute arterial ischaemia: evolution of findings in an in vivo rat model

Abstract: This model shows the correct sequence of events during arterial AMI and demonstrates that MRI can be recommended for early diagnosis of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Thanks to the development of animal model of mesenteric ischemia, it was possible to explore the physiopathological process that conducts to intestinal infarction, underlining that a specific timing of lesions occurs and it is very important to define this to ensure a correct diagnostic assessment and therapeutic result [27]. …”
Section: Resultsmentioning
confidence: 99%
“…Thanks to the development of animal model of mesenteric ischemia, it was possible to explore the physiopathological process that conducts to intestinal infarction, underlining that a specific timing of lesions occurs and it is very important to define this to ensure a correct diagnostic assessment and therapeutic result [27]. …”
Section: Resultsmentioning
confidence: 99%
“…In CP, pericolic fluid was never found; in the injured colonic wall, fibrotic reaction develops leading to continuous mild and irregular circumferential thickening with gaping lumen [18, 19], as observed in 100% of patients, and so, the target sign, due to acute mucosal hemorrhagic and edematous phenomena, is absent (Figure 5). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, investigations have suggested that magnetic resonance imaging (MRI) could play an important role especially in the follow-up of IC [1517]. Considering previous experiences on animal models in which the correct evolution of the small and the large bowel ischemia/infarction was studied and defined [16, 18, 19], a similar evolution of IC can then be expected in humans in which the spectrum of findings remains currently not well understood [20]. …”
Section: Introductionmentioning
confidence: 99%
“…While radiologist are usually familiar with the more common imaging including radiographs, computed tomography (CT), magnetic resonance imaging (MRI) and ultrasound (US) procedures, many are not aware of the significant contributions nuclear medicine can make in the management of patients in acute care [1][2][3][4][5][6][7]. While other radiologic imaging methods depict anatomy and rely on knowledge of normal patterns to recognize abnormal ones, nuclear medicine evaluates organ and physiologic functions.…”
Section: Introductionmentioning
confidence: 99%